Revision of Hestiasulini Giglio-Tos, 1915 stat. rev. (Insecta: Mantodea: Hymenopodidae) of Borneo, with description of new taxa and comments on the taxonomy of the tribe - Schwarz, Christian J.; Shcherbakov, Evgeny (Zootaxa, 2017)
The Bornean Oxypilinae species previously included in the genus Hestiasula Saussure, 1871 are revised. External morphology and genital characters of Sundaian taxa differ considerably from the Indian type species H. brunneriana Saussure, 1871, necessitating taxonomic and nomenclatural changes. The genus Catestiasula Giglio-Tos, 1915 is reinstated. It is characterized by the apomorphic partial fusion of the dorsal and ventral laminae of the left phallomere, and by the complete reduction of the apical process. It is represented on Borneo with two species, C. nitida (Brunner de Wattenwyl, 1893) and C. moultoni Giglio-Tos, 1915. An additional species, C. seminigra (Zhang, 1992) n. comb. occurs in continental SE Asia. Two new genera are described, united by the lack of styli, the presence of dorsal carinae on the subgenital plate, and the unique morphology of the dorsal lamina of the left phallomere, but differing in the morphology of head and forelegs. Astyliasula gen. nov. accommodates A. phyllopus (De Haan, 1842) n. comb. and related species from the Sunda Islands and continental SE Asia: A. basinigra (Zhang, 1992) n. comb., A. hoffmanni (Tinkham, 1937) n. comb., A. javana (Beier, 1929) n. comb., A. major (Beier, 1929) n. comb., A. inermis (Wood-Mason, 1879) n. comb., and A. wuyshana (Yang & Wang, 1999) n. comb.. Hestias sarawaca Westwood, 1889 is removed from synonymy with A. phyllopus and reinstated as A. sarawaca (Westwood, 1889) n. comb.. The monotypic taxon Pseudohestiasula borneana gen. nov. sp. nov. is erected for a Bornean endemic more closely related to Astyliasula than to the other genera. Hestiasula is now restricted to H. brunneriana and related species from India and adjacent countries. The tribe Hestiasulini Giglio-Tos, 1915 stat. rev. is proposed for all genera more closely related to Hestiasula than to other Oxypilinae, that is Hestiasula, Ephestiasula, Catestiasula, Astyliasula, and Pseudohestiasula. New data on the ecology and distribution of all Bornean Hestiasulini as well as a key to the Oxypilinae of Borneo are provided.